International Brand Management of Chinese Companies Case Studies on the Chinese Household Appliances and Consumer Electronics Industry Entering US and Western European Markets - Bell, Sandra (Contributions to Economics,, 2008)
This book is a must read for all those interested in building successful global brands and for all those interested in China and Chinese companies - A strange combination? No. Based on extensive research and interviews with Lenovo, Haier, TCL, Hisense and key decision makers worldwide, Sandra Bell gives reasons and identifies a Chinese way of international brand management. She reveals: - Who are Chinese branded companies? Where are they coming from, where are they heading for? What are their strengths and weaknesses regarding branding, marketing and going global? - How does an appropriate brand strategy look like, when Chinese branded companies enter developed markets in the US and Western Europe? What can they learn from successful brands from Japan and Korea? - How have Lenovo, Haier, TCL and Hisense entered the US and Western European markets so far? To what extend have they followed the recommended brand approach. What did they decide differently and why? Read the book and discover yourself.